Pemahaman Informal Murid Tahun Lima Tentang Perkadaran (Sains Humanika, 2017)
This study aims to identify primary school pupils' informal understanding and solving problems strategies related to proportional. This qualitative study involved Year Five pupils who were selected through purposive sampling. Data were collected using clinical interview technique can show the pupils' strategies and in-depth justification for each activity is shown. This article presents the analysis of the pupils' responses related to two proportional tasks. Data shows that students used various informal strategies to solve proportional problems. The findings also showed that students who have not learn ratio and proportion topic formally, could show proportional reasoning elements, such as unitizing, partitioning, and changes and quantities. The findings of this study may provide information to mathematics teachers that every student has different informal strategy to solve proportional problems based on their experiences and prior knowledge. Thus teachers need to diversify activities to encourage students' proportional thinking.
Keywords: Informal understanding; proportional problems; strategies